The Effects of Digital Financial Literacy and Perceived Risks on the Decision to Use Digital Banks (A Case Study of Gen Z In Malang City) - Simanjuntak, Lusiana Br; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The high public decision to use Digital Bank shows the public's acceptance of Digital Bank. Digital Banks are present to attract people's attention by offering interest rates that exceed the guarantee limit by LPS, so Digital Financial Literacy and Risk Perception are important before making a decision. This study aims to analyze how the influence of Digital Financial Literacy and Risk Perception on the Decision to Use Digital Banks among Gen Z in Malang City. This research is a survey-based quantitative method with primary data sources, namely questionnaires. Purposive sampling is a technique in sampling, where in this study, the Lemeshow formula was used so that 100 respondents were obtained. Binary Logistic Regression Analysis method is used in this study so that it is found that digital financial literacy has a positive effect on the decision to use digital banks and risk perception has a negative effect on the decision to use digital banks.